UPAYA KEPALA SEKOLAH MELALUI KEBIJAKAN YANG DIAMBIL TERKAIT PERMASALAHAN ANAK BERKEBUTUHAN KHUSUS PADA SISTEM EDUCATION FOR ALL MELALUI PENDIDIKAN INKLUSI DI SEKOLAH DASAR - Wina Apriana, Juwita Sari , Saswitri Indra, Efna Yulita; Tenti Putri Handayani; Juwita Sari; Indah , Iwit Sunarti , Weni Yulastri (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
Education is a fundamental right for every individual, including children with special needs (CWSN). In an effort to realize an equitable and child-friendly education system, the principle of Education for All (EFA) serves as both a global and national foundation for the implementation of inclusive education in Indonesia. As an initial level of formal education, elementary schools hold a strategic role in implementing inclusive education to ensure that all students, including CWSN, receive quality and equitable educational services. However, the implementation of inclusive education in elementary schools still faces various challenges, including limited facilities and infrastructure, teacher competencies, adaptive curricula, and social stigma toward CWSN. This study aims to analyze the role of school principals through the policies they adopt in addressing issues related to CWSN within the Education for All system through inclusive education in elementary schools. The method used is a literature review by examining various academic publications from the past ten years. The results of the review show that school principals have a central role in formulating policies such as initial assessment, provision of accessibility facilities, development of adaptive curricula, teacher training, and fostering an inclusive school culture. In addition, collaboration between school principals, teachers, parents, and the community is key to the successful implementation of inclusive education. This study recommends strengthening inclusive leadership among school principals based on humanistic values and the principles of social justice in managing basic education services for CWSN.